2008
DOI: 10.1002/chir.20506
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of efficacy of chiral adrenergic agonists

Abstract: The origin of terms, affinity, intrinsic activity (or efficacy) and spare receptors has been reviewed. The Easson-Stedman theory (1933) in relation to the activation of adrenoceptors by agonists proved to be useful in the analysis of affinity and efficacy. Eudismic ratios of agonists provided critical information about the receptor-mediated activation. The evidence from circular dichroism spectroscopy with a fluorescent-tagged adrenoceptor agonist indicates a stereoselective interaction with the receptor. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The initial pharmacologic observations have been supported by numerous studies that have confirmed that the chirality of the β‐OH carbon affects binding kinetics, affinities and agonist activities, see Ref. 12. For example, results from site‐directed mutation studies suggest that the differences in binding affinity and stimulation of adenylyl cyclase activity observed with ( R )‐ and ( S )‐isoproterenol were associated with enantioselective binding interactions between the β‐OH moiety and the Asn‐293 residue in TM6 with the R ‐configuration producing the more favorable complex 13.…”
Section: Enantioselective Binding Of Agonists To the β2‐armentioning
confidence: 89%
See 1 more Smart Citation
“…The initial pharmacologic observations have been supported by numerous studies that have confirmed that the chirality of the β‐OH carbon affects binding kinetics, affinities and agonist activities, see Ref. 12. For example, results from site‐directed mutation studies suggest that the differences in binding affinity and stimulation of adenylyl cyclase activity observed with ( R )‐ and ( S )‐isoproterenol were associated with enantioselective binding interactions between the β‐OH moiety and the Asn‐293 residue in TM6 with the R ‐configuration producing the more favorable complex 13.…”
Section: Enantioselective Binding Of Agonists To the β2‐armentioning
confidence: 89%
“…A primary structural feature of most β 2 ‐AR agonists is the presence of a hydroxyl moiety on the β‐carbon, see Figure 1. The importance of the chirality of the β‐carbon stereocenter on agonist activity was initially demonstrated in 1908 by Cushny who determined that ( R )‐(–)‐epinephrine constricted the blood vessels of frogs more effectively than its ( S )‐(+)‐enantiomer 12. The initial pharmacologic observations have been supported by numerous studies that have confirmed that the chirality of the β‐OH carbon affects binding kinetics, affinities and agonist activities, see Ref.…”
Section: Enantioselective Binding Of Agonists To the β2‐armentioning
confidence: 97%
“…Recently it was postulated that FPRs expressed in the vomeronasal organs of mammals have an olfactory function associated with the identification of pathogenic states [35], and Bufe et al [36] found that these receptors exhibited stereo-selective preference for peptides containing D-amino acids. Although numerous GPCR have been characterized as enantioselective receptors [18;19;37], including odorant receptors [38], only one example of enantioselective recognition of non-peptide ligands by FPRs has been observed previously [9]. The growing evidence implicating anti-inflammatory and tissue-protective effects of FPR agonists [16;17] and the recent development of novel chiral ligands as potential therapeutics and agonists of various GPCR [18;19;39] prompted us to search for novel non-peptide small-molecule enantiomeric FPR agonists [12;15].…”
Section: Discussionmentioning
confidence: 99%
“…Stereochemical information plays an important role in GPCR recognition processes [18;19]. Stereoselectivity suggests direct and specific receptor targeting, and identification of such stereospecific interactions may have important consequences in drug discovery and development, such as improvement of pharmacokinetic properties and removing undesirable side effects of agents by virtue of the unique activity of enantiomers [20-22].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a large number of studies has elaborated the concept that (Ϫ)-stereoisomers of catecholamines bind to adrenergic receptors with higher affinity and activate the receptors with higher potency than the corresponding (ϩ)-stereoisomers. This concept has recently been covered in an excellent review (Patil et al, 2008).…”
Section: Different Efficacies Of Gpcr Ligand Stereoisomersmentioning
confidence: 99%